Analysis of risk-factors associated with diarrhea prevalence among underfive children in Galkayo District Puntland State, Somalia - Isack, Mustaf A.; Nyamai, Juma J.; Kerochi, Atei (International Journal Of Community Medicine And Public Health, 2021)
Background: The study analysed risk factors associated with diarrhea prevalence among underfive children in Galkayo District Puntland State, Somalia. Methods: The study used analytical cross-sectional survey conducted in Galkayo, from February to March 2020. The inclusion criteria were caregivers with underfive children, and exclusion criteria were children over five years, caregivers who have no underfive children and children with chronic diarrhea. Sample of 385 was calculated using Yamane formula. Caregivers were randomly selected using simple random sampling after cluster sampling. The researcher administered structured questionnaires, collected data from eligible caregivers using interview guide and elicited on diarrhea perceptions. Quantitative data was analysed using SPSS, qualitative data was identified common and sub-themes. Results: The study found diarrhea was affecting 30% of underfive children. The presence of two under-fives in the household was associated with high diarrhea prevalence [OR=1.93, 95% CI= (1.21, 3.08)]. Low educational level of underfive caregivers were associated with high diarrhea occurrence [OR=1.36, 95% CI= (0.68, 2.66)]. Households headed by non-biological mothers, diarrhea prevalence was high [OR=0.06, 95% CI= (0.00, 0.50) and OR=0.17, 95% CI= (0.03, 0.79)] respectively. Those children under the care of employed caregivers, diarrhea occurrence was high [OR=2.41 (0.99, 5.80)]. Poor personal hygiene (32%), sanitation (28%), and water quality (28%) were attributed to the cause of diarrhea among children. Conclusions: The study recommends, practice of child spacing, improve caregivers’ basic education to better understand risk factors and seek treatment, establish routine water quality surveillance at source and at household level, conduct awareness behaviour change by promotion of handwashing.